Parental Perceptions of the Importance of Islamic Religious Education for Early Childhood at Cahaya Bintang Kindergarten - Dewi, Elok Faroita; Lukman, Syaiful (Journal of Educational Research and Practice, 2024)
This research describes parents' perceptions of the importance of Islamic religious education for early childhood at Cahaya Bintang KB/TK, Perum Pesona Bukit Batuah, Graha Indah, North Balikpapan, Balikpapan City. This research uses a qualitative case study approach based on the results of a survey conducted by researchers, parents' awareness of the importance of Islamic religious education in early childhood shows that there is still a lot of diversity, namely positive perceptions and negative perceptions. Positive perception is the perception that Islamic religious education is important in everyone's life, and negative perception is the perception that Islamic religious education is not important in everyday life. There are several reasons that cause this difference in perception, including: 1) Parents' understanding of Islamic religious education is lacking. 2) Lack of understanding of what motivates children to study Islamic religious education and 3) Weak economic sector causes limited ability of parents to support their children and provide opportunities for their children to obtain a good education and deepen their understanding of Islamic religious education